Ethical review of COVID-19 research in the Netherlands; a mixed-method evaluation among medical research ethics committees and investigators - IJkema, R.; Janssens, M. J. P. A.; van der Post, J. A. M.; Licht, C. M. (PloS one, 2021)
During the beginning of the COVID-19 pandemic there was an urgent need for accelerated review of COVID-19 research by Medical Research Ethics Committees (MRECs). In the Netherlands this led to the implementation of so-called 'fast-track-review-procedures' (FTRPs) to enable a swift start of urgent and relevant research. The objective of this study is to evaluate FTRPs of MRECs in the Netherlands during the COVID-19 pandemic and to compare them with the regular review procedures (RRPs). An explanatory sequential mixed method study was conducted. Online questionnaires and four group interviews were conducted among MREC representatives and investigators of COVID-19 research. In addition, data from a national research registration system was requested. Main outcome measures are differences in timelines, quality of the review and satisfaction between FTRPs and RRPs. The total number of review days was shorter in FTRP (median 10.5) compared to RRPs (median 98.0). Review days attributable to the MRECs also declined in FTRPs (median 8.0 versus 50.0). This shortening can be explained by installing ad hoc (sub)committees, full priority given to COVID-19 research, regular research put on hold, online review meetings and administrative leniency. The shorter timelines did not affect the perceived quality of the review and ethical and legal aspects were not weighted differently. Both MREC representatives and investigators were generally satisfied with the review of COVID-19 research. Weaknesses identified were the lack of overview of COVID-19 research and central collaboration and coordination, the delay of review of regular research, and limited reachability of secretariats. This study shows that accelerated review is feasible during emergency situations. We did not find evidence that review quality was compromised and both investigators and MRECs were content with the FTRP. To improve future medical ethical review during pandemic situations and beyond, distinguishing main and side issues, working digitally, and (inter)national collaboration and coordination are important.